Optimal portfolio diversification in the Asia-Pacific region incorporating currency risk and interest rate term premiums - Kaw, Kelvin Jon Wua (2008)
The dissertation explores the concept of time-varying international portfolio allocation from the perspective of a global investor holding the world portfolio, diversifying in toe the Asia-Pacific region. The paper involves the application of the International CAPM framework to generate optimal holding, employing a QTARCH process to model time-varying quantities and prices of risk.